Characterisation of tissue homing CD8+ T cells in a murine cytomegalovirus model - O'Hara, G (2013)
Experimental T cell-inducing vaccines seek to generate rapidly responsive, tissue-homing, antigen-specific T cells. CMV induces an unusual memory population (memory "inflation") of highly differentiated effector memory CD8+ T cells specific for a subset of epitopes and as such is being tested as a vaccine vector. Clearly understanding of the factors involved in memory inflation and tissue-associated CD8+ T cells generated by CMV will aid vaccine design and is of general relevance for tissue protection and pathology. I sought to examine the IL-18/ IL-18Rα axis in the murine cytomegalovirus model and its potential role in the maintenance of memory inflation or the function of such cells in vivo. IL-18 receptor expression has been linked to tissue-homing IL-17 secreting cells in human and in the final chapter I explored potentially equivalent populations in mice. MCMV induces increased expression of IL-18rα on tissue-associated antigen specific, (M38+ and m45+), cells in highly significant fashion at both 7 days post infection (dpi) up to 150 dpi (p < 0.05 for using paired t-tests). Both IL-18Rα and IL-18 were dispensable in the development of memory inflation. I observed, however, that control of viremia was impaired in mice lacking IL-18Rα but not IL-18. IL-18Rα+ T cells in mice infected with MCMV can rapidly secrete IFNγ when exposed to IL-12 and IL-18 in the absence of cognate antigen. MCMV infected C57BL/6 mice are protected from infection with Listeria monocytogenes and Mycobacterium tuberculosis in a time-dependent manner. However this protection is abrogated by removal of IL-18Rα or IL-18. These data are consistent with the idea that non-cognate functioning of T cells is protective against pathogens. This is the first report showing protection induced by a common pathogen against distinct unrelated pathogens is IL-18/IL-18Rα dependent. My data support a role for induced T cells. Such findings have significant implications in man, both for the pathogenesis of human disease and for vaccine design.